Dimensionamento e sequenciamento de lotes no segmento de eletrodomésticos de linha branca - Bergamini, Fernanda Paula (2019)
In this work we address the optimization of the production of household appliances in a white line segment. The main characteristics of this production process are maximum number of lot breaks per time period; production lines in parallel and with different speeds that vary according to the type of product; the multiple capabilities with multiple product models; and capacity constraints in the manufacturing process and availability of productive hours. Such characteristics are motivated by the real case of a company that operates in the white line segment. We investigate new optimization models to represent the problem of sizing and sequencing of production batches for the white line segment, in order to minimize the processing time of the production and reduce the amount of batch fractionation in production, meeting the demand request. The decisions are treated independently, due to the complexity of the actual situation studied. The results of computational tests with instances based on actual data show that the proposed optimization approaches, both for the production batch sizing and for the sequencing of these batches, presented good solutions for the case under study. In the experiments carried out, it was possible to reduce the processing time of the production, which was the main objective, besides the opportunity to gain productivity with the implementation of the models proposed. It should be noted that the motivation for this work arose from a difficulty of the company to meet the scheduled delivery. To solve this difficulty, the executive board decided to create a collaboration between the factory and the university to find an adequate solution strategy. Thus, this work also allows the reduction of the gap between theory and practice through a real case study, contributing to the approximation between academia and industry.